Humorous Situations Created by Violations and Floutings of Conversational Maxims in a Situation Comedy Entitled How I Met Your Mother - Amianna, Jenna Nadia Rasbi Putri; Putranti, Adventina (Universitas Sanata Dharma, 2017)
As a form of communication that evokes laughter, humor is seen as one of important aspects in building relationship with people. Linguists suggest that humor exists because there is noncooperative interaction among interlocutors resulting from not observing Cooperative Principle in the conversations. Related to that, this study aims to analyze humorous situations in a situation comedy entitled How I Met Your Mother Season 2, Episodes 1 to 5 which are created by violating and flouting the conversational maxims as the forms of not observing the Cooperative Principle. Keywords: humorous situation, cooperative principle, flouting, violation